The effect of biological anti-TNF-α therapy, originator and biosimilar, used to treat ankylosing spondylitis was studied based on clinical and blood counts and an inflammatory marker - Husham A. Aldaoseri; Naael Hussein Ali; Fires Al-Mubarak (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Ankylosing spondylitis (AS) is a common inflammatory rheumatic disease that affects the axial skeleton. It causes inflammatory back pain, structural and functional problems, and a lower quality of life. If an AS patient does not respond to NSAIDs, the FDA has approved several anti-TNF therapy originators and biosimilars. This study aims to determine how well anti-TNF treats ankylosing spondylitis using a traditional complete blood count, clinical signs, and inflammatory markers. Blood samples were collected from 81 AS patients from two groups: 67 AS patients treated with anti-TNF therapy and 14 newly diagnosed patients who were not given treatment (naïve); in addition, 65 healthy individuals were enrolled in the study as a control group. The complete blood count showed a significant difference between the three groups in lymphocyte, neutrophil, and platelet counts (P = 0.001). Positive controls (14/14) treated with NSAIDs had higher disease activity than established patients (32/67) treated with an anti-TNF drug (P = 0.0001). There is a higher significant difference in inflammatory markers between patients with AS and positive controls than in healthy individuals (p = 0.001). In conclusion, AS patients had decreased activity with anti-TNF therapy but progressed on radiographic examination.